PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN TOTAL ASSETS TURN OVER TERHADAP SISA HASIL USAHA PADA KPRI MARDI RAHAYU RSUD BREBES - Sri Rahayu (Jurnal Strategik, 2017)
ABSTRACT This study aims to determine the effect of the current ratio, debt to equity ratio, net profit margin and total assets turn over to changes in the remaining operating results at KPRI Mardi Rahayu Regional Hospital Brebes partially and simultaneously. From the results of the study it can be concluded: the influence of the current ratio and the debt to equity ratio partially on changes in the remaining business results do not have a significant effect on changes in residual results of operations at KPRI Mardi Rahayu RSUD Brebes, but net profit margin and total assets turn over partially to changes the remaining business results do not have a significant effect on changes in the remaining results of operations at KPRI Mardi Rahayu RSUD Brebes. Simultaneous testing of the current ratio, debt to equity ratio, net profit margin and total assets turn over to changes in the remaining operating results at KPRI Mardi Rahayu RSUD Brebes has a significant influence on changes in the remaining operating results at KPRI Mardi Rahayu General Hospital Brebes, determination coefficient of 98,30%, while the remaining 1,70% is influenced by other variables outside the variables studied. Keywords: Current Ratio, Debt To Equity Ratio, Net Profit Margin, Total Assets Turn Over And Remaining Operating Results